Microbiology of the skin and the role of biofilms in infection - Percival, Steven L (Int Wound J, 2011)
The integrity of human skin is central to the prevention of infection. Acute and chronic wounds can develop when the integrity of skin as a barrier to infection is disrupted. As a multi‐functional organ, skin possesses important biochemical and physical properties that influence its microbiology. These properties include a slightly acidic pH, a low moisture content, a high lipid content (which results in increased hydrophobicity) and the presence of antimicrobial peptides. Such factors have a role to play in preventing exogenous microbial colonisation and subsequent infection. In addition, the properties of skin both select for and enhance colonisation and biofilm formation by certain ‘beneficial’ micro‐organisms. These beneficial micro‐organisms can provide further protection against colonisation by potential pathogens, a process known as colonisation resistance. The aim of this paper is to summarise the microflora of skin and wounds, highlighting the role of certain micro‐organisms and biofilms in associated infections.